Akselerasi Minat Belajar Mahasiswa STT Paulus Jakarta Melalui Pembelajaran Berbasis Teknologi Pendidikan - Petrus Elkana Atto (STT Pelita Dunia, 2026)
This study aims to investigate the enhancement of student learning engagement and interest through the implementation of educational technology-based pedagogy at STT Paulus Jakarta. This research employed a descriptive qualitative approach. Data were gathered through interviews, observations, and documentation, and subsequently analyzed utilizing descriptive statistics. The findings demonstrate that the integration of technology specifically Learning Management Systems (LMS), interactive media, and online discussion platforms significantly elevates student learning interest. This improvement is evidenced by increased active participation, heightened intellectual curiosity toward the instructional materials, and greater autonomous learning. Furthermore, the flexibility of access to learning resources serves as a primary facilitating factor. Conversely, certain constraints persist, notably limited digital literacy and restricted internet connectivity. Consequently, institutional support and the advancement of digital competencies for both faculty members and students are imperative. This study concludes that educational technology-based instruction effectively fosters student learning interest and holds profound relevance for implementation within theological education.